The Relationship Between Tourism Development with Primary Forest in Indonesia - Simatupang, Aldo Gadra Paulus; Soetjipto, Widyono (Department of Urban and Regional Planning, Diponegoro University, 2025)
To further develop Indonesian tourism, the Indonesian government designed a program to develop 10 new Indonesian